Size limits of magnetic-domain engineering in continuous in-plane exchange-bias prototype films - Gaul, Alexander; Emmrich, Daniel; Ueltzhöffer, Timo; Huckfeldt, Henning; Doğanay, Hatice; Hackl, Johanna; Khan, Muhammad Imtiaz; Gottlob, Daniel M.; Hartmann, Gregor; Beyer, André; Holzinger, Dennis; Nemšák, Slavomír; et al. (Beilstein Journal of Nanotechnology, 2018)
Background: The application of superparamagnetic particles as biomolecular transporters in microfluidic systems for lab-on-a-chip applications crucially depends on the ability to control their motion. One approach for magnetic-particle motion control is the superposition of static magnetic stray field landscapes (MFLs) with dynamically varying external fields. These MFLs may emerge from magnetic domains engineered both in shape and in their local anisotropies. Motion control of smaller beads does necessarily need smaller magnetic patterns, i.e., MFLs varying on smaller lateral scales. The achievable size limit of engineered magnetic domains depends on the magnetic patterning method and on the magnetic anisotropies of the material system. Smallest patterns are expected to be in the range of the domain wall width of the particular material system. To explore these limits a patterning technology is needed with a spatial resolution significantly smaller than the domain wall width.Results: We demonstrate the application of a helium ion microscope with a beam diameter of 8 nm as a mask-less method for local domain patterning of magnetic thin-film systems. For a prototypical in-plane exchange-bias system the domain wall width has been investigated as a function of the angle between unidirectional anisotropy and domain wall. By shrinking the domain size of periodic domain stripes, we analyzed the influence of domain wall overlap on the domain stability. Finally, by changing the geometry of artificial two-dimensional domains, the influence of domain wall overlap and domain wall geometry on the ultimate domain size in the chosen system was analyzed.Conclusion: The application of a helium ion microscope for magnetic patterning has been shown. It allowed for exploring the fundamental limits of domain engineering in an in-plane exchange-bias thin film as a prototypical system. For two-dimensional domains the limit depends on the domain geometry. The relative orientation between domain wall and anisotropy axes is a crucial parameter and therefore influences the achievable minimum domain size dramatically.
Keywords: exchange bias; helium ion microscopy; ion bombardment induced magnetic patterning; magnetic domains; magnetic nanostructures

(untitled) - Aradhya, S. V.; Rowlands, G. E.; Oh, J.; Ralph, D. C.; Buhrman, R. A. (Nano Lett., 2016)

(untitled) - Moon, K.-W.; Kim, D.-H.; Yoo, S.-C.; Je, S.-G.; Chun, B. S.; Kim, W.; Min, B.-C.; Hwang, C.; Choe, S.-B. (Sci. Rep., 2015)

(untitled) - Fassbender, J.; Poppe, S.; Mewes, T.; Juraszek, J.; Hillebrands, B.; Barholz, K.-U.; Mattheis, R.; Engel, D.; Jung, M.; Schmoranzer, H.; Ehresmann, A. (Appl. Phys. A: Mater. Sci. Process., 2003)

(untitled) - Ehresmann, A.; Koch, I.; Holzinger, D. (Sensors, 2015)

(untitled) - Höink, V.; Sacher, M. D.; Schmalhorst, J.; Reiss, G.; Engel, D.; Junk, D.; Ehresmann, A. (Appl. Phys. Lett., 2005)

(untitled) - Zingsem, N.; Ahrend, F.; Vock, S.; Gottlob, D.; Krug, I.; Doganay, H.; Holzinger, D.; Neu, V.; Ehresmann, A. (J. Phys. D: Appl. Phys., 2017)

(untitled) - Ahrend, F.; Holzinger, D.; Fohler, M.; Pofahl, S.; Wolff, U.; DeKieviet, M.; Schaefer, R.; Ehresmann, A. (J. Magn. Magn. Mater., 2015)

(untitled) - Jarosz, A.; Holzinger, D.; Urbaniak, M.; Ehresmann, A.; Stobiecki, F. (J. Appl. Phys., 2016)

(untitled) - Rapoport, E.; Beach, G. S. D. (Appl. Phys. Lett., 2012)

(untitled) - Donolato, M.; Vavassori, P.; Gobbi, M.; Deryabina, M.; Hansen, M. F.; Metlushko, V.; Ilic, B.; Cantoni, M.; Petti, D.; Brivio, S.; Bertacco, R. (Adv. Mater., 2010)

(untitled) - Sarella, A.; Torti, A.; Donolato, M.; Pancaldi, M.; Vavassori, P. (Adv. Mater., 2014)

(untitled) - Burn, D. M.; Atkinson, D. (Appl. Phys. Lett., 2013)

(untitled) - Brandl, F.; Franke, K. J. A.; Lahtinen, T. H. E.; van Dijken, S.; Grundler, D. (Solid State Commun., 2014)

(untitled) - Albisetti, E.; Petti, D.; Madami, M.; Tacchi, S.; Vavassori, P.; Riedo, E.; Bertacco, R. (AIP Adv., 2017)

(untitled) - McGrouther, D.; Nicholson, W. A. P.; Chapman, J. N.; McVitie, S. (J. Phys. D: Appl. Phys., 2005)

(untitled) - Potzger, K.; Bischoff, L.; Liedke, M. O.; Hillebrands, B.; Rickart, M.; Freitas, P. P.; McCord, J.; Fassbender, J. (IEEE Trans. Magn., 2005)

(untitled) - Devolder, T. (Phys. Rev. B, 2000)

(untitled) - Kaminsky, W. M.; Jones, G. A. C.; Patel, N. K.; Booij, W. E.; Blamire, M. G.; Gardiner, S. M.; Xu, Y. B.; Bland, J. A. C. (Appl. Phys. Lett., 2001)

(untitled) - Konings, S.; Miguel, J.; Luigjes, J.; Schlatter, H.; Luigjes, H.; Goedkoop, J.; Gadgil, V. (J. Appl. Phys., 2005)

(untitled) - Terris, B. D.; Thomson, T. (J. Phys. D: Appl. Phys., 2005)

(untitled) - Bernas, H.; Traverse, A. (Appl. Phys. Lett., 1982)

(untitled) - Berthold, I.; Müller, M.; Klötzer, S.; Ebert, R.; Thomas, S.; Matthes, P.; Albrecht, M.; Exner, H. (Appl. Surf. Sci., 2014)

(untitled) - Schuppler, C.; Habenicht, A.; Guhr, I. L.; Maret, M.; Leiderer, P.; Boneberg, J.; Albrecht, M. (Appl. Phys. Lett., 2006)

(untitled) - Bürger, D.; Zhou, S.; Pandey, M.; Viswanadham, C. S.; Grenzer, J.; Roshchupkina, O.; Anwand, W.; Reuther, H.; Gottschalch, V.; Helm, M.; Schmidt, H. (Phys. Rev. B, 2010)

(untitled) - Albisetti, E.; Petti, D.; Pancaldi, M.; Madami, M.; Tacchi, S.; Curtis, J.; King, W. P.; Papp, A.; Csaba, G.; Porod, W.; Vavassori, P.; Riedo, E.; et al. (Nat. Nanotechnol., 2016)

(untitled) - Schmidt, C.; Smolarczyk, M.; Gomer, L.; Hillmer, H.; Ehresmann, A. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2014)

(untitled) - Devolder, T.; Chappert, C.; Chen, Y.; Cambril, E.; Bernas, H.; Jamet, J. P.; Ferré, J. (Appl. Phys. Lett., 1999)

(untitled) - Choi, S. D.; Joo, H. W.; Lee, S. S.; Hwang, D. G.; Choi, J. H.; Lee, K. A.; Kim, S.; Bae, S. (J. Appl. Phys., 2007)

(untitled) - Fassbender, J.; Poppe, S.; Mewes, T.; Mougin, A.; Hillebrands, B.; Engel, D.; Jung, M.; Ehresmann, A.; Schmoranzer, H.; Faini, G.; Kirk, K. J.; Chapman, J. N. (Phys. Status Solidi A, 2002)

(untitled) - Mougin, A.; Poppe, S.; Fassbender, J.; Hillebrands, B.; Faini, G.; Ebels, U.; Jung, M.; Engel, D.; Ehresmann, A.; Schmoranzer, H. (J. Appl. Phys., 2001)

(untitled) - Ueltzhöffer, T.; Schmidt, C.; Krug, I.; Nickel, F.; Gottlob, D.; Ehresmann, A. (J. Appl. Phys., 2015)

(untitled) - McGrouther, D.; Chapman, J. N.; Vanhelmont, F. W. M. (J. Appl. Phys., 2004)

(untitled) - Hyndman, R.; Warin, P.; Gierak, J.; Ferré, J.; Chapman, J. N.; Jamet, J. P.; Mathet, V.; Chappert, C. (J. Appl. Phys., 2001)

(untitled) - Zheng, M.; Yu, M.; Liu, Y.; Skomski, R.; Liou, S. H.; Sellmyer, D. J.; Petryakov, V. N.; Verevkin, Y. K.; Polushkin, N. I.; Salashchenko, N. N. (Appl. Phys. Lett., 2001)

(untitled) - Huckfeldt, H.; Gaul, A.; Müglich, N. D.; Holzinger, D.; Nissen, D.; Albrecht, M.; Emmrich, D.; Beyer, A.; Gölzhäuser, A.; Ehresmann, A. (J. Phys.: Condens. Matter, 2017)

(untitled) - Costner, E. A.; Lin, M. W.; Jen, W.-L.; Willson, C. G. (Annu. Rev. Mater. Res., 2009)

(untitled) - Pease, R. F.; Chou, S. Y. (Proc. IEEE, 2008)

Helium Ion Microscopy - Hlawacek, G.; Gölzhäuser, A. (Springer, 2016)

(untitled) - O’Grady, K.; Fernandez-Outon, L. E.; Vallejo-Fernandez, G. (J. Magn. Magn. Mater., 2010)

(untitled) - Müglich, N. D.; Merkel, M.; Gaul, A.; Meyl, M.; Götz, G.; Reiss, G.; Kuschel, T.; Ehresmann, A. (New J. Phys., 2018)

(untitled) - Tanase, M.; Petford-Long, A. K.; Heinonen, O.; Buchanan, K. S.; Sort, J.; Nogués, J. (Phys. Rev. B, 2009)

(untitled) - Ziegler, J. F.; Ziegler, M. D.; Biersack, J. P. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2010)

(untitled) - Holzinger, D.; Zingsem, N.; Koch, I.; Gaul, A.; Fohler, M.; Schmidt, C.; Ehresmann, A. (J. Appl. Phys., 2013)

Magnetic Domains - Hubert, A.; Schäfer, R. (Springer, 1998)

Interagency Report NISTIR - Donahue, M. J.; Porter, D. G. (National Institute of Standards and Technology, 1999)

Scanning Electron Microscopy - Reimer, L. (Springer Berlin, 1998)

(untitled) - Ehresmann, A.; Schmidt, C.; Weis, T.; Engel, D. (J. Appl. Phys., 2011)

(untitled) - Schütz, G.; Wagner, W.; Wilhelm, W.; Kienle, P.; Zeller, R.; Frahm, R.; Materlik, G. (Phys. Rev. Lett., 1987)

(untitled) - Stöhr, J.; Wu, Y.; Hermsmeier, B. D.; Samant, M. G.; Harp, G. R.; Koranda, S.; Dunham, D.; Tonner, B. P. (Science, 1993)

(untitled) - Berkov, D. V.; Boone, C. T.; Krivorotov, I. N. (Phys. Rev. B, 2011)

Nanostrukturforschung und Nanotechnologie - Hartmann, U. (Oldenbourg Wissenschaftsverlag, 2012)

Chemie der Elemente - Greenwood, N. N.; Earnshaw, A. (VCH Verlagsgesellschaft, 1989)

(untitled) - Ehresmann, A.; Junk, D.; Engel, D.; Paetzold, A.; Röll, K. (J. Phys. D: Appl. Phys., 2005)

(untitled) - Hoffmann, H. (Phys. Status Solidi, 1964)

(untitled) - Mauri, D.; Kay, E.; Scholl, D.; Howard, J. K. (J. Appl. Phys., 1987)